Simulation-based User-centered Design: An Approach to Device Development during COVID-19. Issue 4 (28th July 2021) - Colman, Nora; Saldana, Christopher; Craig, Kentez; Edwards, Nicole; McGough, Jennifer; Mason, Carrie; Hebbar, Kiran B.
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Since the onset of COVID-19, intubations have become very high risk for clinical teams. Barrier devices during endotracheal intubation protect clinicians from the aerosols generated. Simulation-based user-centered design (UCD) was an iterative design process used to develop a pediatric intubation aerosol containment system (IACS). Simulation was anchored in human factor engineering and UCD to better understand clinicians' complex interaction with the IACS device, elicit user wants and needs, identify design inefficiencies, and unveil safety concerns. Methods: This study was a prospective observational study of a simulation-based investigation used to design a pediatric IACS rapidly. Debriefing and Failure Mode and Effect Analysis identified latent conditions related to 5 device prototypes. Design iterations made were based on feedback provided to the engineering team after each simulation. Results: Simulation identified 32 latent conditions, resulting in 5 iterations of the IACS prototype. The prototypes included an (1) intubation box; (2) IACS shield; (3) IACS frame with PVC pipes; (4) IACS plexiglass frame, and finally, (5) IACS frame without a plexiglass top. Conclusions: Integration of simulation with human factor ergonomics and UCD, in partnership with mechanical engineers, facilitated a novel context to design and redesign a pediatric IACS to meet user needs and address safety concerns.